Measuring the influence of discharge energy on white layer thickness in electrical discharge machining process. (January 2019) - Muthuramalingam, T.
Graphical abstract: Highlights: Due to uniform energy distribution, iso current produced low AVLT. Vi has most dominating nature in EDM process. The Duty factor has considerably contributed on the surface roughness. Abstract: In electrical discharge machining, the performance measures are mainly influenced by the discharge energy developed during the machining process. Owing to its higher strength, stainless steel can be easily machined by electrical discharge machining under the presence of dielectric medium. Since the surface quality of high strength workpiece is influenced by white layer formation, it is very essential to analyze the effects of discharge energy distribution and process parameters on white layer formation in machining process. In the present study, an endeavor has been attempted to analyze the influence of a modified pulse energy generator system on performance measures. From the experimental results, it has been observed iso energy pulse generator has created thinner and more symmetrical white layer thickness on the machined workpiece owing to its ability to produce lower discharge energy pulses with nearly uniform energy distribution. Peak current has been observed as significant factor on determining white layer formation in the EDM process.